The Myth of Chornobyl in Contemporary Ukrainian Drama Plots - Pavlova, О.М. (Видавництво НДУ ім. Миколи Гоголя, 2018)
In the article the author considers the process of creating the modern myth – the exclusion zone – in the plays "Third Prayer" by Ya. Vereshchak, "Lost Fugitives" by Neda Nezhdana, "At the Beginning and at the End of Time" by P. Arie. Major attention has been focused on identifying modern aspects of the reception of the Chornobyl technogenic catastrophe: the overlapping and convergence of archaic and social myths, model of initiation; the correlation of the concept "Us"/"Them"; the peculiarities of the "memory" and "recollections" of those events; the artistic representation of the archetypal images of Land/Home; the decoding of the mental code of nation in the post-apocalyptic period.
Keywords: memory; plot; archetype; initiation